RESPONSE OF ACCELERATED AGEING ON SEEDS OF RADISH (RAPHANUS SATIVUS L.) CV. ARKA NISHANTH - C., DEEPIKA; B. C., CHANNAKESHAVA; PITAGI, ANITA (The Bioscan, 2016)
A Laboratory experiment was conducted at Department of Seed Science and Technology,GKVK, UAS, Bangalore during summer 2014 to assess the response of accelerated ageing on seeds of radish (RaphanussativusL.)cv. Arka nishanth.The resultant seeds of gibberllic acid and micronutrients of seedswas subjected to the accelerated ageing at 45±20 C for 100% RH for various time intervals (0, 2, 4, 6, 8,10days) and seed quality tests of the seed material completed (germination percentage, shoot length, root length, mean seedling length, mean seedling dry weight, seedling vigour index I&II, electrical conductivity), before and after ageing treatments. The seed showed a gradual and sequential reduction in germination percentage and seedling vigour as accelerated ageing duration increased. Seedleachate conductivity increased with ageing duration.